1986
DOI: 10.1288/00005537-198610000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of perineural spread in squamous carcinomas of the head and neck

Abstract: The occurrence and prognostic implications of perineural spread were examined in 239 patients with mucosal squamous carcinomas of the head and neck. Perineural spread was demonstrated in resections from 64 patients (27%), the majority having primary tumors at one of three sites: buccal cavity, larynx, and pharynx. Perineural spread near nodal metastases was uncommon. There was no evidence that perineural involvement was more commonly associated with large tumors or less differentiated ones. No association was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
1
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(113 citation statements)
references
References 14 publications
8
98
1
6
Order By: Relevance
“…Previous studies by Soo et al (8) reported that the survival rate of patients with laryngeal cancer were reduced from 49 to 23% following 3 years of treatment if the patients developed PNI. In the past, the pathogenic model of laryngeal cancer with PNI was considered to be associated with the lymphatic dissemination of tumor cells within the nerve (8). However, this model was later rejected, since the lymphatic channels do not penetrate the inner sanctum of the nerve sheath.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies by Soo et al (8) reported that the survival rate of patients with laryngeal cancer were reduced from 49 to 23% following 3 years of treatment if the patients developed PNI. In the past, the pathogenic model of laryngeal cancer with PNI was considered to be associated with the lymphatic dissemination of tumor cells within the nerve (8). However, this model was later rejected, since the lymphatic channels do not penetrate the inner sanctum of the nerve sheath.…”
Section: Discussionmentioning
confidence: 97%
“…In the 7th edition of the AJCC staging system for the classification of squamous cell carcinomas, published in 2010, PNI was included among the high-risk factors for patients with laryngeal cancer (16). Previous studies by Soo et al (8) reported that the survival rate of patients with laryngeal cancer were reduced from 49 to 23% following 3 years of treatment if the patients developed PNI. In the past, the pathogenic model of laryngeal cancer with PNI was considered to be associated with the lymphatic dissemination of tumor cells within the nerve (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a, c, d), where the above mentioned variables were the main prognostic factors involved except for the DM incidence which was affected mainly by solid pathologic pattern of growth. By analyzing each single significant factor, perineurial invasion has already shown its association with a high local failure in head and neck cancers [22], and the reason lays in the correlated high probability of residual microscopic disease in adjacent tissues. In contrast with this, positive microscopic resection margins status resulted in our case series to be a strong predictor in all survival analyses for all parotid malignancies rather than the ACC, suggesting a more important prognostic role acted by other pathologic variables such PNI and solid pattern of growth.…”
Section: Discussionmentioning
confidence: 99%
“…These features were identified in our histopathological sections. In 239 patients with mucosal squamous carcinomas of the head and neck, PNS was demonstrated in resections of 64 patients (27%), the majority having primary tumors at one of three sites: buccal cavity, larynx, and pharynx [5].…”
Section: Discussionmentioning
confidence: 99%